Lesson Learned of Good Practices for Educational Management of Thai Local Administrative Organizations: Case Studies of the 3 Model Educational Institutes - hunpayon, surasavadee; kaewkumkong, ampa; jaiborisudhi, watunyu (King Prajadhipok’s Institute Journal, 2020)
The objective of this article is to explore the lessons learned and good practices of the model educational institutes under the Local Administrative Organizations (LAO), which adopt a specific management approach according to the guidelines of the Department of Local Administration. This concept supports decentralization of power from the central authority to educational institutes. The research methodology involves the use of case study research, selecting three educational institutes regarded as models of School-Based Management for Local Development (SBMLD). These institutes represent all the regions and cover basic education, higher education, and non-formal and informal education. This research collects data from field studies coupled with interviews with relevant people. The results show that LAOs have decentralized power to all three institutes, both directly and indirectly, allowing the institutes to take control of decision-making and self-management. That reflects freedom and flexibility in management. Although certain hindrances in decentralization of education are still found, there are important co-factors that enable the educational administration of the model schools to develop at a rapid pace, especially in the area of far-sighted local leaders and the commitment in local education, and an organizational culture that focuses on participatory management. Consequently, the model institutes cultivate and adopt good practices in accordance with SBMLD, encompassing various aspects of general administration, academic management, budget management, and personnel management.